Extensive Diversity of Viruses in Millipedes Collected in the Dong Nai Biosphere Reserve (Vietnam) - Litov, Alexander G.; Semenyuk, Irina I.; Belova, Oxana A.; Polienko, Alexandra E.; Thinh, Nguyen Van; Karganova, Galina G.; Tiunov, Alexei V. (Viruses, 2024)
Advances in sequencing technologies and bioinformatics have led to breakthroughs in the study of virus biodiversity. Millipedes (Diplopoda, Myriapoda, Arthropoda) include more than 12,000 extant species, yet data on virus diversity in Diplopoda are scarce. This study aimed to explore the virome of the millipedes collected in the Dong Nai Biosphere Reserve in Vietnam. We studied 14 species of millipedes and managed to assemble and annotate the complete coding genomes of 16 novel viruses, the partial coding genomes of 10 more viruses, and several fragmented viral sequences, which may indicate the presence of about 54 more viruses in the studied samples. Among the complete and partial genomes, 27% were putative members of the order Picornavirales. Most of the discovered viruses were very distant from the viruses currently present in the relevant databases. At least eight viruses meet the criteria to be recognized as a new species by the International Committee on Taxonomy of Viruses, and, for two of them, a higher taxonomic status (genus and even family) can be suggested.